Student’s Perceptions of Youglish as Instructional Technology and Media for Learning English Pronunciation - Sukmawati; Vivit Romayanti; Andi Tenri Abeng; Muliaty Ibrahim; Hasanuddin; Andi Rasmiyati (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2024)
Fluency in pronunciation is a crucial aspect of effective verbal communication. Inaccurate pronunciation can result in a misinterpretation of the word's intended meaning. Consequently, it is imperative to have media resources that assist pupils in comprehending pronunciation better. There are numerous media platforms available, one of them being YouGlish. The research aims to investigate students' perception on the the use of Youglish as instructional technology and media for learning English pronunciation. YouGlish is a website that utilizes YouTube videos to enhance English pronunciation. The researchers employed the descriptive qualitative method in this study. This study was carried out for second semester English students. The instruments utilized in this investigation consisted of a questionnaire and an interview. The data indicates that students hold favorable views regarding the utilization of YouGlish. The research findings demonstrated the students' viewpoint regarding the use of YouGlish for enhancing English Pronunciation learning. The survey findings also indicated predominantly favorable and unfavorable feedback. The utilization of both of these instruments is the method to ascertain the students' perspectives on the integration of YouGlish in pronunciation acquisition. Ultimately, YouGlish has the ability to pique students' interest in studying Pronunciation and foster a desire to learn. In conclusion that YouGlish has the ability to generate students' interest in studying by virtue of its online platform, which may actively engage them with a fervent enthusiasm for learning the subject matter.